Effects of Late Evening Snack on Cirrhotic Patients: A Systematic Review and Meta-Analysis - Ying-jie Guo; Zi-bin Tian; Na Jiang; Xue-li Ding; Tao Mao; Xue Jing (Gastroenterology Research and Practice)
Background. Energetic effects of late evening snack (LES) on cirrhotic patients were reported recently, but there was no quantitative analysis. In this meta-analysis, we reviewed and quantified the effects of LES on energy metabolism and substrate oxidation in the patients with cirrhosis, which will be of benefit for liver cirrhosis nutritional therapy. Methods. A systematic search was conducted in PubMed, Embase, Web of Science, Elsevier, China National Knowledge Infrastructure, and Wanfang Database for relevant trials published until July 2017. These studies statistically were combined and analyzed by RevMan 5.3. Results. Fourteen trials comprising 478 cases were eligible for analysis. The results showed that the respiratory quotient value (MD = 11.09) and carbohydrate oxidation value (MD = 0.05) significantly elevated with one week or with up to three weeks of LES treatment in cirrhotic patients (P<0.05). Meanwhile, the levels of serum albumin (MD = 2.98) and cholinesterase (SMD = 1.09) were increased with LES administration for three weeks or that lasting twelve weeks (P<0.05). However, there was no significant improvement for the levels of alanine aminotransferase (ALT) (P=0.53), aspartate aminotransferase (AST) (P=0.96), and total bilirubin (TB) (P=0.32). Conclusions. LES could improve the energy malnutrition state of cirrhotic patients. However, it may have little effect on reducing liver parenchymal injury indexes such as serum aminotransferase.